The Role of the Third Gender in The Isan LukThung literature - ทิพนา, สันติ (Research and Development Journal Sisaket Rajabhat University, 2022)
The objective of this research paper was to study the role of the third gender in Isan luk thung literature. By studying the content of Thai luk thung songs that reflect the role of the third gender in Isan society, the results of the research found that The physical characteristics of transgender women in the Isan Lukthung literary song mention their shape, appearance, and dress. They contain content to create humor, such as hip-headed pansexual, belly-bottomed pansexual, rural pansexual, etc. They are more clownish and aim to reduce tension. of people in society and also serves to relieve suffering to find happiness for oneself and the people in society The role of the physical characteristics of the third gender to create color for society acceptance of people in society Or sometimes there may be claims for the rights of the third gender through Isaan luk thung literature. It is intended to be entertaining. Because most people view the third gender as a clown. That will serve to relieve suffering and bring happiness to oneself. The social role of the third gender Third gender is now accepted and open. It is not enough to enable these groups of people to live happily in society. and equal to the common people or have the same rights as other people. In addition, some people in society also see that these groups of people are abnormal and need to be corrected. Some have knowledge, abilities, can do many benefits. to the nation but had to endure insults because of their gender The third gender has a clear mind. Outwardly cheerful but inside it may be repetitive always be scolded and was seen as a clown In addition, luk thung literary songs that are related to the third gender often raise issues of heartbreak because of being abandoned by men, being deceived, etc.